(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Using discourse analysis, this paper examines the female readers’ attitudes towards fashion and clothing which were expressed in their letters published in the journal Women’s world: the organ of Serbian women’s charity associations. The first part of the paper describes the programme and dominant ideology of fashion that was promoted in the journal. That ideology is then compared to opinions and attitudes that are expressed in the letters of female readers. Final analysis observes the connection between fashion and notions of tradition, moral, and emancipation of women.